2018
DOI: 10.1016/j.wneu.2018.03.208
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Properties of Intraoperative Ultrasound in Glioma Surgery and Factors Associated with Gross Total Tumor Resection

Abstract: The specificity of intraoperative US is good, but sensitivity for detecting the last milliliter is low compared with postoperative MRI. Tumor volume and tumor depth are the predictors of achieving gross total resection, although ultrasound image quality was not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 58 publications
(64 reference statements)
0
31
2
1
Order By: Relevance
“…Munkvold et al reported a series of 144 gliomas operated using NUS. 8 Their cohort of gliomas had a higher proportion of LGGs (33% vs 17%) and more recurrent cases (40% vs 20%) compared with our series. Munkvold Values are presented as number (%) of patients unless otherwise indicated.…”
Section: Discussioncontrasting
confidence: 57%
“…Munkvold et al reported a series of 144 gliomas operated using NUS. 8 Their cohort of gliomas had a higher proportion of LGGs (33% vs 17%) and more recurrent cases (40% vs 20%) compared with our series. Munkvold Values are presented as number (%) of patients unless otherwise indicated.…”
Section: Discussioncontrasting
confidence: 57%
“…They determined that tumor volume and tumor depth were the main factors that influenced the sensitivity for intraoperative US to detect residual tumor; small superficial tumors being more likely to be completely resected. 29 One can infer that the impact of the usage of intraoperative US on the clinical course of patients with brain tumors is related to the ability to locate and better resect these lesions.…”
Section: Discussion Intraoperative Ultrasound In Neurosurgerymentioning
confidence: 99%
“…Specificity was higher in LGG than in HGG (94 and 77%) and lowest in patients who undergone previous radiotherapy. The Authors conclude their analysis stating that ioUS specificity is high while the sensitivity for small residue is lower than post-operative MRI (22).…”
Section: Intraoperative Ultrasound In Glioma Surgerymentioning
confidence: 99%
“…Numerous studies have also investigated the diagnostic properties of ioUS in terms of sensitivity, specificity and ability to increase EOR and subsequently PFS and OS (9, 1922).…”
Section: Introductionmentioning
confidence: 99%